2015
DOI: 10.5505/agri.2015.55706
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Chronic Pain After İngunial Hernia Repair

Abstract: Summary Objectives: The percentage of chronic pain in adults having inguinal hernia repair is 5-35%. Although this pain is thought to be related to some reasons, there is not an exact conclusion about this. In this study, the aim was to point out the incidence of chronic pain ÖzetAmaç: İnguinal herni onarımı sonrası erişkinlerde %5-35 oranında kronik ağrı gelişmektedir. Bu ağrının; uygulanan cerrahi tekniğe, ameliyat öncesi ve sonrası ağrıya, hastanın psikososyal ve fizyolojik yapısına veya diğer nedenlere bağ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Aasvang and Kehlet searched the literature between January 2000 -May 2004 and found that the risk of CPSP was 12% [30]. Karaman et al found that the incidence of pain, 3 months after surgery was 18.6% [31]. It is possible that the recognition of CPSP has increased after 2000 and as the prevention gained importance, the incidence might have declined.…”
Section: Discussionmentioning
confidence: 99%
“…Aasvang and Kehlet searched the literature between January 2000 -May 2004 and found that the risk of CPSP was 12% [30]. Karaman et al found that the incidence of pain, 3 months after surgery was 18.6% [31]. It is possible that the recognition of CPSP has increased after 2000 and as the prevention gained importance, the incidence might have declined.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of pain after open inguinal hernia repair has been reported to be the highest on the first postoperative day [ 1 ]. Untreated postoperative pain or a high pain score within 24 h of surgery may lead to persistent pain after inguinal hernia repair [ 3 , 4 ]. Patients with prolonged pain have an increased duration of hospitalization and may fail to return to their daily lives [ 5 ].…”
Section: Introductionmentioning
confidence: 99%